Selective phosphorylation of AMPA receptor contributes to the network of long-term potentiation in the anterior cingulate cortex - Song, Qian; Zheng, Hongwei; Kuner, Thomas (The journal of neuroscience, 2017)
Phosphorylation of AMPA receptor GluA1 plays important roles in synaptic potentiation. Most previous studies have been performed in the hippocampus, while the roles of GluA1 phosphorylation in the cortex remain unknown. Here we investigated the involvement of the phosphorylation of GluA1 in the LTP in the anterior cingulate cortex (ACC) using mice with a GluA1 knock-in mutation at the PKA phosphorylation site serine 845 (s845A) or CaMKII/PKC phosphorylation site serine 831 (s831A). The network LTP, which is constructed by multiple recordings of LTP at different locations within the ACC, was also investigated. We found that the expression of LTP and network LTP was significantly impaired in the s845A mice, but not in the s831A mice. By contrast, basal synaptic transmission and NMDA receptor-mediated responses were not affected. Furthermore, to uncover potential information under the current acquired data, a new method for reconstruction and better visualization of the signals was developed to observe the spatial localizations and dynamic temporal changes of fEPSP signals and multiple LTP responses within the ACC circuit. Our results provide strong evidence that PKA phosphorylation of the GluA1 is important for the network LTP expression in the ACC. SIGNIFICANCE STATEMENT: Previous studies have shown that PKA and PKC phosphorylation of AMPA receptor GluA1 plays critical roles in LTP in the hippocampus, while the roles of GluA1 phosphorylation in the cortex remain unknown. In the present study, by combining a 64-channel multielectrode system and a novel analysis and visualization method, we observed the accurate spatial localization and dynamic temporal changes of network fEPSP signals and LTP responses within the ACC circuit and found that PKA phosphorylation, but not PKC phosphorylation, of the GluA1 is required for LTP in the ACC.